Modelling the long‐term deformation of the sedimentary substrate of Mt. Etna volcano (Italy). (29th June 2015) - Scudero, Salvatore; De Guidi, Giorgio; Imposa, Sebastiano; Currenti, Gilda
Abstract This study investigates in detail the deformation events that have affected the sedimentary successions forming the substrate of Mt. Etna volcano (Italy). Based on the geometric reconstruction of a buried sedimentary marker, we have been able to identify and quantify the effects of three different mechanisms of deformation that have affected the area in the last 600 ka. Numerical results from Finite Element Method (FEM) applied to model viscoelastic deformation suggest the occurrence of a crustal doming process originating at the mantle‐crust transition (~16 km). We propose that the source of deformation is related to the diapiric uprise of hydrothermal material originating in altered ocean‐like crust and its emplacement at a shallower level in the crust. This process has great relevance in the volcanic system and should be considered for the full assessment of its origin and evolution.